Role of Booster Dose on Antibody Titer after Recombinant Hepatitis B Vaccination (Journal of Medicine, 2009)
Hepatitis B virus infection is an important public health problem with significant morbidity and mortality. Recombinant hepatitis B vaccination for the prevention of hepatitis B virus infection is in practice in different parts of the world since its availability in 1986. Government of Bangladesh has also included hepatitis B vaccine in EPI schedule since 2005. This study was carried out to assess the seroconversion status among hepatitis B vaccinated individuals. A total of 190 individuals including 150 vaccinated persons and 40 non-vaccinated apparently healthy individuals were included as study population. Sources of vaccinated persons were from both EPI and non-EPI schedule of vaccination. Age and sex matched non-vaccinated individuals served as controls for the study. All individuals constituting the study population were screened for HBsAg by Immunochromatographic strip test and only HBsAg-negative persons were included for estimation of their anti-HBs titer. Out of 150 vaccinated individuals, 133(88.67%) were found to have anti-HBs titer in the protective level (e"10 IU/L), while 17(11.33%) individuals had anti-HBs titer below the protective level (